La familia y su incidencia en el comportamiento social de los niños de preparatoria, primer grado de educación básica de la escuela fiscal mixta “Cuarto Centenario” nº 1 sección matutina, periodo lectivo 2013 - 2014 - Álvarez Sánchez, Maritza Beatriz (2014)
This thesis entitled: THE FAMILY AND ITS IMPACT ON BASIC EDUCATION FIRST DEGREE CHILDREN SOCIAL BEHAVIOR “CUARTO CENTENARIO” SCHOOL Nº 1 MORNING SECTION 2013 – 2014. It has been developed according to the rules of graduation National University of Loja. In the present investigation the General Objective was: To show the importance of family and its impact on the Social. The methods used were: Scientist, Analytical - Synthetic, Inductive - Deductive, Descriptive, and Statistical Model, the same that were used to describe and explain the shape and the relationship between the family and their impact on the social behavior of children. For the field research , a survey conducted by Parents, for the structure and modes of being of the family and as an impact on the social behavior of children; and with an observation guide applied directly to children from the first years of basic education, which allowed it to evaluate different aspects of social behavior. According to the results of the survey of parents, 44% indicated that the family is structured by father and mother; while only 25% is structured by the mother and children; 5% is only made up of other family members. As for the ways of being family 55% that the type of parents that there are authoritarian; 20% say they are overprotective parents; other parents indicated that there are 20% permissive parents; and, 5% indicates that there democratic parents. From the results of the observation guide we have that 100% of children damaged school supplies ; while 75% of children do not respect the school furniture ; 50% of children do not respect their teacher ; children by 95% disqualify her parents when asked of the family ; there is a 90% of aggressive children ; have aggressive attitudes disqualify her friends as putting names on 90% disciminate like a child whose physical conditions 95% of children suggest punishments for their peers and teacher verbally and physically threaten their peers, and not maintain 100% correct behavior in school social events.